The utility of magnetic resonance imaging (MRI) in diagnosing hemosiderosis of long term hemodialysis patients - Taniguchi, Toshio; Nishi, Osamu; Akagaki, Youji; Murata, Tamaki; Uchino, Hitomi; Sako, Mamoru (Journal of Japanese Society for Dialysis Therapy, 1992)
The utility of magnetic resonance imaging (MRI) in diagnosing hemosiderosis (H) was evaluated in patients on long-term hemodialysis. The study subjects were 19 patients with serum ferritin (Ft) ≥300μg/l and 4 patients with Ft<300μg/l served as controls, for a total of 23 patients on long-term hemodialysis receiving MRI examination. As a result, the intensity of the liver was diffusely reduced on T2 images in all 19 patients with Ft≥300μg/l The severity of hemosiderosis was divided into groups designated 0 to III according to the degree of siderosis as evaluated by MRI. In a patient of severity I, the T1 image was normal and the intensity was reduced only on the T2 image. In a patient of severity III, the intensity was reduced on both T1 and T2 images. On the other hand, both T1 and T2 images showed normal liver intensity in all 4 controls with Ft<300μg/l. Furthermore, the results of liver function tests including GOT and GPT were normal in all 23 patients. The MRI-assessed severity of H (0 to III) correlated positively with serum Ft and serum Fe. These results suggest that the T1 image is useful for evaluating the severity of H, the T2 image for early diagnosis and that MRI and Ft are useful for evaluating the therapeutic effects on hemosiderosis.